GLOBALISATION AND TRADE UNIONS CHALLENGES: NIGERIAN MANUFACTURING SECTOR EXPERIENCE - Ishola, Genty Kabiru (European Scientific Journal, ESJ, 2013)
Today, the globalisation of the world market has brought about several competitions on local companies which invariably have an adverse effect on trade union density due to unfavourable macroeconomic policies used for the promulgation of globalisation. The movement from Social regulation to Labour Market Control, created this competitions all in the name of productivity enhancement and efficiency creation. The study examines the challenges brought by globalisation and all what accompany the concept while the role of Trade Unions was also measured to overcome the flexibility brought by globalisation. The study uses secondary information with discourse analysis of existing literatures on the subject matter to have a position. It was reveal that globalisation created more vacuums than integration among Workers of the North and South due to competition postulated by globalisation.